2019
DOI: 10.1002/chem.201903816
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenative Arylation of Carboxylic Acids by Aryl Migration

Abstract: An unprecedented deoxygenative arylationo f aromatic carboxylic acids has been achieved, allowing the construction of an enhanced libraryo fu nsymmetrical diaryl ketones.T he synergistic photoredox catalysis and phosphoranyl radical chemistrya llows for precise cleavage of as tronger CÀOb ond and formation of aw eaker CÀC bond by 1,5-arylm igrationu nder mild reaction conditions. This new protocol is independent of substrate redox-potential,e lectronic, and substituent effects. It affords ag eneral and promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…5) and found that many commercially available aromatic bromides can be used to deliver the desired ketones (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in good yields. The excellent functional group tolerance of -COOR (28,33,44,45), -CN (29, 34), terminal unsaturated chemical bonds (43,44), and heteroarenes (38)(39)(40)(41)(42)(43)46) support the practicality of the reaction. With this strategy, it is also very easy to construct fluorineand fluoroalkylcontaining diaryl ketones (30-32, 36, 37, 39-42) with acceptable yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5) and found that many commercially available aromatic bromides can be used to deliver the desired ketones (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in good yields. The excellent functional group tolerance of -COOR (28,33,44,45), -CN (29, 34), terminal unsaturated chemical bonds (43,44), and heteroarenes (38)(39)(40)(41)(42)(43)46) support the practicality of the reaction. With this strategy, it is also very easy to construct fluorineand fluoroalkylcontaining diaryl ketones (30-32, 36, 37, 39-42) with acceptable yields.…”
Section: Resultsmentioning
confidence: 99%
“…This could simplify and upgrade ketone synthesis from carboxylic acids and organic halides 13 . Very recently, our group and Doyle et al reported an elegant photoredoxpromoted mild deoxygenation of carboxylic acids generating acyl radicals [31][32][33][34][35] . Since photoredox and nickel-catalyzed C-O bond formation between carboxylic acids and aromatic bromides has been reported 36 to achieve the desired crosselectrophile coupling, acyl radical oxidative addition by a metallaphotoredox pathway [37][38][39][40][41] is essential to suppress the C-O bond formation (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following from their previous work on intramolecular hydroacylation from carboxylic acids, the Zhu group reported an intramolecular deoxygenative arylation to form diarylketones 79 (Scheme 18). [43] This reaction follows a similar initial pathway, with the formation of the triphenylphosphine radical cation and subsequent deoxygenation to form the acyl radical 80 . This radical then undergoes an ipso 1,6‐addition to the aryl sulfonamide to form intermediate 81 , followed by extrusion of SO 2 to give the aminyl radical 82 .…”
Section: Radicals From Deoxygenation and Desulfurisation Reactionsmentioning
confidence: 98%
“…In this context, Zhu and co‐workers described a photoredox‐mediated deoxygenative aryl migration of aromatic carboxylic acids to allow the efficient synthesis of unsymmetrical diaryl ketone scaffolds (Scheme 16). [19] …”
Section: C−c Bond Formationmentioning
confidence: 99%